A new approach of reduction of carbon dioxide emission and optimal use of carbon and hydrogen content for the desired syngas production from coal. (20th August 2020) - Lu, Wenyang; Cao, Qingxi; Xu, Bang; Adidharma, Hertanto; Gasem, Khaled; Argyle, Morris; Zhang, Fan; Zhang, Yulong; Fan, Maohong
Abstract: This research is designed to make progress in overcoming the challenges through the development of a two-stage coal processing. Specifically, a two-stage process was used to maximize the use of the carbon in coal or increase the carbon monoxide yield or lower carbon dioxide and methane yields. Carbon dioxide-char gasification in the absence of water can generate carbon monoxide with near-zero methane, which is desired to produce high-carbon and low-hydrogen chemicals such as oxalic acid through catalytic carbon monoxide coupling and hydrolysis. The technology is applicable to any coal, although Power River Basin (PRB) coal is used as an example feedstock in this research Also, the sodium-iron catalyst can accelerate not only the reaction kinetics in both stages but also increase the hydrogen/carbon monoxide ratio in the syngas produced in the second stage. In other words, the catalyst is a multifunctional agent, which can not only intensify the overall coal process efficiency but also improve the qualities of the desired syngas products and reduce carbon dioxide emission. Thus, In the 1st stage, the catalysts can significantly reduce the CO2 -char gasification by as high as 75.00%. In the 2nd stage, the H2 /CO ratio of ideal syngas is ∼2:1 with near-0 CH4 generation and the CH4 production can be reduced as high as 61.29% for the CO2 –H2 O-Char coal gasification. The activation energy for the 2nd stage is reduced by as high as 35.43% than that of raw coal without use Na–Fe catalyst. The overall carbon footprint reduction for the study is reduced by 87.33% in the 1st stage and 96.77% compared to the direct coal combustion. Graphical abstract: Image 1